Program EVALUASI PROGRAM CETAK SAWAH BARU DALAM RANGKA MEWUJUDKAN KETAHANAN PANGAN DI PROVINSI JAMBI: Evaluation Of The New Rice Field Printing Program In Order To Realize Food Security In Jambi Province - Rialdi Syaputra (Jurnal Khazanah Intelektual, 2023)
The fact of the pattern of agricultural land conversion in Jambi Province, changes in the area of food crops are more influenced by economic factors (commodity prices, share of food subsectors) and population growth with a tendency to decline every year. The pattern of agricultural land conversion in Jambi Province is also as a result of the use of cultivated land from food crop land to plantation cropland and the massive expansion of oil palm plantations. The objectives of this study are: Evaluating the implementation of agricultural land expansion through the printing of new rice fields in Jambi Province and Analyzing the sustainability status of the agricultural land expansion program through printing new rice fields in Jambi Province. The results of the evaluation of the rice field printing program in Jambi Province, indicates that the rice field printing program can be implemented as planned. The expansion of the land faced several obstacles. These constraints include limited farm capital, inadequate farming roads and irrigation facilities, insufficient availability of agricultural tools and machinery, market access and locations for expanding distant land and relatively less fertile land and relatively low knowledge and skills of farmers. The results of the MDS analysis, whose analysis includes socio-cultural, economic, ecological, infrastructure and institutional dimensions, show that the rice field printing program in Jambi Province is included in the status of being quite sustainable with a sustainability index value of 52.94. Sustainability status of new rice field printing program It only achieves so because the economic, infrastructure and institutional dimensions are relatively low and fall into the category of less, which is less than 50. Meanwhile, ecological and socio-cultural aspects are the highest index values and are included in the sufficient category. The policy implications that can be taken are as follows: Infrastructure development policies in the form of agricultural business road construction, construction / rehabilitation of tertiary irrigation network facilities, drainage of water discharge and irrigation of sluice circulation and meeting the needs of agricultural tools and machinery (Rice threshing machines, rice plow tractors, three-wheeled vehicles), Optimizing rice paddy farming through Paddy plow tractors, three-wheeled vehicles), Optimizing paddy rice farming through a) increasing productivity by improving varieties, improving cultivation technology and conserving land and water resources; b) increasing the rice paddy planting index by building and expanding the reach of irrigation networks and utilizing water resources optimally, and c) increasing the efficiency of farming through optimal utilization of local resources.